2017
DOI: 10.1080/17453674.2017.1321351
|View full text |Cite
|
Sign up to set email alerts
|

The risk of non-union per fracture: current myths and revised figures from a population of over 4 million adults

Abstract: Background and purposeFracture non-union remains a major clinical problem, yet there are no data available regarding the overall risk of fractures progressing to non-union in a large population. We investigated the rate of non-union per fracture in a large adult population.MethodsNational data collected prospectively over a 5-year period and involving just under 5,000 non-unions were analyzed and compared to the incidence of fracture in the same period.Results and interpretationThe overall risk of non-union pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
167
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 22 publications
6
167
3
4
Order By: Relevance
“…Especially in an aging population, large bone defects and fracture non‐unions constitute major challenges to surgeons . Mills et al . reported that up to 9% of bone fractures lead to non‐unions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in an aging population, large bone defects and fracture non‐unions constitute major challenges to surgeons . Mills et al . reported that up to 9% of bone fractures lead to non‐unions.…”
Section: Introductionmentioning
confidence: 99%
“…reported that up to 9% of bone fractures lead to non‐unions. Because the treatment of a patient with a non‐union costs between EUR 8000 to 91 000, insufficient bone healing represents an enormous economical burden to the healthcare system . Moreover, the outcome of spinal fusion surgeries also depends on the body's capacity to heal bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of fractures heal uneventfully, it takes several months for the bone to heal and it cannot bear weight before it is completely healed. Unfortunately, 5–10% of fractures result in either nonunion or delayed union (2, 3). Moreover, the annual cost of treatment of bone fractures is up to $21 billion in the United States (4).…”
mentioning
confidence: 99%
“…Bone has an intrinsic ability to regenerate but often fails to heal if there is a lack of mechanical stability or vascularization or if the bone defect is too large. Recent analyses of data from a large number of patients demonstrated that non‐unions occur in up to 9% of fractures . The treatment of a patient with a non‐union can cause substantial costs, ranging between €8000 and €91 000 .…”
Section: Clinical Relevance and Current Standard Proceduresmentioning
confidence: 99%